Effects of CFRP on reinforced conventional concrete and ultra high performance concrete frames - Ali, Shahnaz Basim (2017)
In this era, mankind faces lots of threats and misfortunes, one of the biggest threats is earthquake, which destroy building and leave thousands of people dead and homeless, during earthquake load, the first part that lead to buildings failure are the joints. Many researches have been conducted to investigate the effect of the external use and rehabilitee of old structures with Carbon Fiber Reinforced Polymer (CFRP). However, very few researches have been carried out investigating the internal use of the CFRP in the structures. The main objective of this study is, to reinforce the frame beam-column joint with CFRP in order to sustain the seismic load. CFRP bars were implemented into two frames, conventional reinforced concrete (RC) frame and ultra-high performance concrete (UHPC) frame, to investigate the effect of embedded CFRP. Experimental test was conducted on the frames with embedded CFRP, to assess the seismic performance, functionality of the frames subjected to cyclic load, the experimental test showed that the ductility behaviour, overall stiffness and failure mechanism, enhanced in both the RC frame with embedded CFRP and the UHPC with embedded CFRP, where the load capacity increased 26%, 11% respectively, compared with the bare frame. Numerical analysis were also used alongside the experimental test, to evaluate the seismic behaviour of the embedded CFRP in joints. Numerical analysis result showed that, the ultimate load capacity increased in the frames with embedded CFRP in the RC frame and UHPC frame, 23%, 52% respectively. Moreover, a good agreement observed between the experimental test and the numerical analysis. Furthermore, finite element model developed for the RC frame with embedded CFRP in the special finite element program code, static nonlinear and nonlinear dynamic analysis were conducted .The static nonlinear result showed that the capacity of the frame with CFRP increased 66% compared to the bare frame and Nonlinear dynamic analysis showed that the maximum displacement for the frame with CFRP diminished 66% compared to bare frame. The efficiency and capability of embedded CFRP in RC frame and UHPC is proved.